Metastatic Renal Cell Carcinoma to the Descending Colon Presenting as Recurrent Hematochezia - Dhoop, Sudheer (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.